(untitled) (Third Sector Social Economic Review, 2021)
Social media offers many opportunities to businesses and consumers. While it enables businesses to promote their products faster, with less cost and to a wider audience, it also enables consumers to share information about businesses and products. While many digital marketing tools enable businesses to reach consumers and obtain information for consumers, social media is an important digital marketing tool due to its structure that allows instant and two-way communication. The purpose of this study is to examine the relationship between post-purchase consumer behavior and social media perceptions and whether post-purchasing consumer behavior differs in terms of demographic factors in order to investigate the relationship between consumer behaviors. In accordance with this purpose, the questionnaire prepared by using literature on social media usage was applied to 410 consumers living in Kayseri province with convenience sampling method. According to the analysis results of the data obtained, there are no statistically significant differences in post-purchase consumer behaviors on social media in terms of education; In a statement in terms of gender and income; In terms of age, occupation, marital status and time spent on social media statistically significant differences were found in many expressions.